GATA2 mutations and overexpression in pediatric acute myeloid leukemia - Zhenzhen Yang; Xingjuan Wang; Xi Chen; Hu Dou; Yi Huang; Ling Lu; Lin Zou; Junqin Bi; Meng Su; Jie Yu; Liming Bao (Pediatric Hematology Oncology Journal, 2019)
Background: GATA2 is important for the regulation of development and proliferation of early pluripotent hematopoietic precursors, and precise GATA2 expression is critical in myeloid lineage maturation. GATA2 mutations have been reported in acute myeloid leukemia (AML) but only few studies of GATA2 mutations and overexpression in pediatric AML have been reported so far and none was in Chinese populations. Method: We analyzed GATA mutation status and expression state in a cohort of 309 Chinese children with AML. We also assessed the impact of GATA2 mutations and overexpression on outcomes in our pediatric AML cohort. Results: GATA2 mutations were observed in 2.6% of the patients and they were clustered in the ZF1 and ZF2 domains. GATA2 overexpression was detected in 72.7% of the cases, with the highest and lowest expression levels observed in adverse subgroup and favorable subgroup, respectively. In the entire cohort, shorter overall survival (OS) and event-free survival (EFS) showed a stronger correlation with GATA2 overexpression than with normal GATA2 levels (OS: p = 0.021; EFS: p = 0.018). Such an inverse relationship between GATA2 overexpression and survivals was evident among AML patients with normal cytogenetics (OS: p = 0.037; EFS: p = 0.024) and adverse features (OS: p = 0.021; EFS: p = 0.023), but not observed in favorable subgroup (OS: p = 0.323; EFS: p = 0.342), suggesting that the negative influence of GATA2 overexpression on pediatric AML outcomes is risk subgroup specific. Conclusion: Our results demonstrate that GATA2 mutations in pediatric AML are rare, and are primarily clustered in the zinc finger (ZF) domains. Our results suggest that GATA2 overexpression exerts a negative influence on survivals, and the effect is risk subgroup specific in pediatric childhood AML. Keywords: Acute myeloid leukemia, Pediatric, GATA2, Overexpression, Outcome